The rise of Chicago's Black metropolis, 1920-1929 - Reed, Christopher Robert (New Black studies series., 2011)
Christopher Robert Reed describes the rise of Chicago's 'black metropolis' of the 1920s, bringing to life the fleeting vibrancy of this dynamic period of racial consciousness and solidarity. Reed shows how African Americans rapidly transformed Chicago and achieved political and economic recognition.